2021
DOI: 10.2139/ssrn.3870190
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion in Dispersion: Measuring Establishment-Level Differences in Productivity

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…It was also higher than in all the countries in the sample used by Berlingieri et al (2017), except for the services in Chile. The estimates for the U.S. are also lower: 1.9 in 1997-2010 reported by Cunningham et al (2018) and 1.4 in 1977 reported by Syverson (2004). The relatively high level of productivity dispersion may be associated with high regional segmentation in Russia (Gennaioli et al, 2014, see Figure 11).…”
Section: σ-Convergencementioning
confidence: 94%
“…It was also higher than in all the countries in the sample used by Berlingieri et al (2017), except for the services in Chile. The estimates for the U.S. are also lower: 1.9 in 1997-2010 reported by Cunningham et al (2018) and 1.4 in 1977 reported by Syverson (2004). The relatively high level of productivity dispersion may be associated with high regional segmentation in Russia (Gennaioli et al, 2014, see Figure 11).…”
Section: σ-Convergencementioning
confidence: 94%
“…Fourth, our results relate to the work of statistical agencies around the world, who are developing procedures to make publicly available summary statistics from micro data, and in particular industrylevel productivity dispersion (Cunningham et al 2018, Berlingieri, Blanchenay, Calligaris & Criscuolo 2017. A key contribution in this paper is to make a suggestion regarding what statistics should be released, namely 5 quantiles necessary to perform Mc Culloch's (1986) quantile estimation of the four Lévy alpha-stable parameters.…”
Section: Introductionmentioning
confidence: 92%
“…It is well known that productivity varies across establishments, even within detailed industries. For example, Cunningham et al (2022) found that on average an establishment at the 90 th percentile of the total factor productivity (TFP) distribution is about 2.9 times as productive as an establishment at the 10 th percentile within four-digit NAICS manufacturing industries. In a survey article, Syverson (2011) discusses several possible sources of productivity dispersion, including difficult-to-measure factors such as differences in managerial talent and differences in the quality of labor and other inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, measurement of establishment-level productivity would also account for the types of workers the establishment employs and the tasks they perform. Our ultimate goal is to address this limitation by integrating establishment-level 1 See Cunningham et al (2022) for a detailed description of the development of the datasets. DiSP is available at: https://www.bls.gov/productivity/articles-and-research/dispersion-statistics-on-productivity/ and https://www.census.gov/disp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation